2022
DOI: 10.1111/cts.13411
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging patient‐centric sampling for clinical drug development and decentralized clinical trials: Promise to reality

Abstract: Advances in the technologies to enable patient-centric sampling (PCS) have the potential to improve blood sample collection by enabling clinical trial participants to collect samples via self-collection or with the help of a caregiver in their home. Typically, blood samples to assess pharmacokinetics and pharmacodynamics of a drug during clinical development are collected at a clinical site via venous blood draw. In this position paper by the International Consortium for Innovation and Quality in Pharmaceutica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…A recent comprehensive review of PCS devices that are commercially available or in development has showcased a variety of FDA 510(k) cleared and/or CE marked options, indicating their regulatory approval for clinical use. 7 Typically, sample collection is facilitated through finger prick or upper arm methods. The matrix is collected either in dried format or as a liquid, with most devices designed for dried whole blood collection.…”
Section: Advancing Clinical Studies With Pcsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent comprehensive review of PCS devices that are commercially available or in development has showcased a variety of FDA 510(k) cleared and/or CE marked options, indicating their regulatory approval for clinical use. 7 Typically, sample collection is facilitated through finger prick or upper arm methods. The matrix is collected either in dried format or as a liquid, with most devices designed for dried whole blood collection.…”
Section: Advancing Clinical Studies With Pcsmentioning
confidence: 99%
“…Historically, traditional clinical studies have predominantly utilized wet matrix assays, requiring milliliters of plasma or serum samples collected at centralized clinical sites or physician offices via venous blood draw, performed by the trained phlebotomists. 7 However, technological innovations in microsampling techniques, coupled with a series of validation studies and evolving regulatory guidelines, have rendered PCS a viable option for clinical trials. PCS employs devices that require microliter level of blood, enabling participants to collect samples independently or with the assistance of a caregiver at home and ship for analysis without the need for refrigeration where suitable stability has been demonstrated (Figure 1).…”
Section: Advancing Clinical Studies With Pcsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 Compared with traditional venous collection by a phlebotomist at clinical site, self-collection or caregiver-assisted collection methods using capillary blood at-home offers convenience, flexibility, and decreases trial burden for patients. 6 There are multiple at-home PK-sampling options and tools 7,8 primarily utilizing two types of collection devices. One involves a separate lancet for skin prick; and the other is an integrated device to combine skin prick with sample collection in one device.…”
mentioning
confidence: 99%
“…Over the last decade, there has been a growing interest in using at-home and patient-centric sampling (PCS) in clinical trials. Studies led by major pharmaceutical companies 1,2 and a recent cross-company review 3 have explored approaches such as dried blood spot (DBS) sampling in phase III studies, with the stated aim of reducing the logistical challenges of collecting samples from difficult-to-manage patient populations such as those who are elderly, or with Alzheimer's disease, 2,4 or with migraine. 5 Dockendorf et al 6 have identified key factors for digitally enabled patient-centric trials -namely, smart dosing, outpatient or patient-centric sampling, digital biomarkers, and digital platforms.…”
mentioning
confidence: 99%